1998
DOI: 10.1155/1999/62564
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Japanese Herbal Medicine “Sho‐saiko‐to”(TJ‐9) on Interleukin‐12 Production in Patients withHCV‐Positive Liver Cirrhosis

Abstract: Interleukin-12 (IL-12) is an important cytokine for maintainence of normal systemic defense and bioregulation. The Japanese herbal medicine Sho-saiko-to (TJ-9) has been administered to 1.5 million Japanese patients with chronic liver diseases. TJ-9 is known to significantly suppress cancer development in the liver and has macrobiotic effects. In the present study, we examined the in vitro production of IL-12 by circulating mononuclear cells from liver cirrhosis patients and the effects of TJ-9 on IL-12 product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 13 publications
(22 reference statements)
0
28
0
Order By: Relevance
“…73 Extensive clinical use suggested that TJ-9 prevented the development of hepatocellular carcinoma in patients with hepatitis C virus infection. 74 We have previously reported that glycyrrhizin, an extract of licorice, abrogated ethanol plus CCl 4 -induced hepatic fibrogenesis in rats. It reduced liver injury and NF-kB binding activity, as well as the degree of the liver fibrosis.…”
Section: Herbal Medicinementioning
confidence: 95%
“…73 Extensive clinical use suggested that TJ-9 prevented the development of hepatocellular carcinoma in patients with hepatitis C virus infection. 74 We have previously reported that glycyrrhizin, an extract of licorice, abrogated ethanol plus CCl 4 -induced hepatic fibrogenesis in rats. It reduced liver injury and NF-kB binding activity, as well as the degree of the liver fibrosis.…”
Section: Herbal Medicinementioning
confidence: 95%
“…Few reports reported hepatotoxic events and death associated with consumption D. dasycarpus with other herbal preparation (128,129,130,131). Additionally, Kampo medicine including DaiSaiko-to and Syo-saiko-to consists of mixture of herbs that has been used as a remedy of several illnesses like dyspepsia and pyretic diseases (10,133). However, these herbal medicine have been linked with some cases of hepatotoxicity (132,134).…”
Section: Discussionmentioning
confidence: 99%
“…However, these herbal medicine have been linked with some cases of hepatotoxicity (132,134). Accordingly, the toxic agents responsible for hepatotoxicity of these kampo herbs are glycyrrhiza, and scutellaria constituents (132,133). Moreover, the mechanism by which these herbs induce hepatotoxicity is not fully understood (132).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations